Bronchiectasis and rheumatoid arthritis: a clinical study. Issue 11 (November 1993) - McMahon, M J; Swinson, D R; Shettar, S; Wolstenholme, R; Chattopadhyay, C; Smith, P; Johns, P; Crosby, N H
Abstract : OBJECTIVES--To examine the relation between rheumatoid arthritis (RA) and bronchiectasis (BR). METHODS--Disease activity, outcome, extra-articular manifestations, and laboratory features were compared in 32 patients with BR and RA (RA-BR group), 32 matched patients with RA without BR (RA group), and 31 patients with BR but without arthritis (BR group). RESULTS--In 30 of the 32 (94%) patients with RA-BR, BR preceded RA. There was no functional or radiological difference between the RA-BR and RA groups, and except for xerophthalmia, which was more common in patients with RA-BR than patients with RA, there was no difference in extra-articular or laboratory features. CONCLUSIONS--Bronchiectasis does not lead to a more aggressive disease course in RA and, despite the recognised association, BR is not an extra-articular manifestation of rheumatoid disease.